Performance Evaluation of microPET: A High-Resolution Lutetium Oxyorthosilicate PET Scanner for Animal Imaging - Chatziioannou, Arion F. (1999)
A new dedicated PET scanner, microPET, was designed and developed at the University of California, Los Angeles, for imaging small laboratory animals. The goal was to provide a compact system with superior spatial resolution at a fraction of the cost of a clinical PET scanner. METHODS: The system uses fiberoptic readout of individually cut lutetium oxyorthosilicate (LSO) crystals to achieve high spatial resolution. Each microPET detector consists of an 8 × 8 array of 2 × 2 × 10-mm LSO scintillation crystals that are coupled to a 64-channel photomultiplier tube by optical fibers. The tomograph consists of 30 detectors in a continuous ring with a 17.2-cm diameter and fields of view (FOVs) of 11.25 cm in the transaxial direction and 1.8 cm in the axial direction. The system has eight crystal rings and no interplane septa. It operates exclusively in the three-dimensional mode and has an electronically controlled bed that is capable of wobbling with a radius of 300 µm. We describe the performance of the tomograph in terms of its spatial, energy and timing resolution, as well as its sensitivity and counting-rate performance. We also illustrate its overall imaging performance with phantom and animal studies that demonstrate the potential applications of this device to biomedical research. RESULTS: Images reconstructed with three-dimensional filtered back projection show a spatial resolution of 1.8 mm at the center of the FOV (CFOV), which remains < 2.5 mm for the central 5 cm of the transaxial FOV. The resulting volumetric resolution of the system is < 8 µL. The absolute system sensitivity measured with a 0.74 MBq (20 µCi) (68)Ge point source at the CFOV is 5.62 Hz/kBq. The maximum noise equivalent counting rate obtained with a 6.4-cm diameter cylinder spanning the central 56% of the FOV is 10 kcps, whereas the scatter fraction is 37% at the CFOV for an energy window of 250–650 keV and the same diameter cylinder. CONCLUSION: This is the first PET scanner to use the new scintillator LSO and uses a novel detector design to achieve high volumetric spatial resolution. The combination of imaging characteristics of this prototype system (resolution, sensitivity, counting-rate performance and scatter fraction) opens up new possibilities in the study of animal models with PET.